The Role of the Educator in Adult Education - Georgios Giannoukos; Georgios Besas; Christos Galiropoulos; Vasilios Hioctour (Journal of Education and Learning (EduLearn), 2015)
The educator in adult education according to the theory of Andragogy, social change and transformative learning is to work towards achieving positive change by coordinating the learning procedure in a way that enables the learner to overcome certain false believes he has due to social conditioning, his working environment and the way in which he has learned.